Rapamycin resistance is linked to defective regulation of Skp2 - Totary-Jain, H.; Sanoudou, D.; Dautriche, C. N.; Schneller, H.; Zambrana, L.; Marks, A. R. (Cancer ResCancer ResCancer Res, 2012)
The mammalian target of rapamycin (mTOR) plays a role in controlling malignant cellular growth. mTOR inhibitors, including rapamycin (sirolimus), are currently being evaluated in cancer trials. However, a significant number of tumors are rapamycin resistant. In this study, we report that the ability of rapamycin to downregulate Skp2, a subunit of the ubiquitin protein ligase complex, identifies tumors that are sensitive to rapamycin. RNA interference (RNAi)-mediated silencing of Skp2 in human tumor cells increased their sensitivity to rapamycin in vitro and inhibited the growth of tumor xenografts in vivo. Our findings suggest that Skp2 levels are a key determinant of antitumor responses to mTOR inhibitors, highlighting a potentially important pharmacogenomic marker to predict sensitivity to rapamycin as well as Skp2 silencing strategies for therapeutic purposes.
Keywords: *Drug Resistance, Neoplasm; Animals; Antibiotics, Antineoplastic/*pharmacology; Cell Line, Tumor; Cyclin-Dependent Kinase Inhibitor p27/analysis; HeLa Cells; Humans; Mice; Phosphorylation; PTEN Phosphohydrolase/physiology; S-Phase Kinase-Associated Proteins/analysis/genetics/*physiology; Sirolimus/*pharmacology; TOR Serine-Threonine Kinases/*antagonists & inhibitors; Xenograft Model Antitumor Assays